Digital Tranformation of Sport Tourism Management through the Implementation of Sport Tourism App 5.0 in Kemumu Village: Tranformasi Digital Pengelolaan Wisata Olahraga melalui Penerapan Sport Tourism App 5.0 di Desa Kemumu - Septian Raibowo; Vika Fitranita; Dewi Suranti; Bogy Restu Ilahi (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to promote digital transformation in sport tourism management in Kemumu Village, North Bengkulu Regency, through the implementation of Sport Tourism App 5.0. The activity employed a Participatory Action Research (PAR) approach involving 40 participants from tourism groups (Pokdarwis), MSME actors, and youth organizations (Karang Taruna). The stages included needs analysis, digital literacy training, application implementation, and evaluation using the Kirkpatrick model. The results indicated an improvement in community digital literacy by 29.3%, with 70% of participants actively using the application for tourism promotion and online booking. Moreover, MSME transactions increased by 45%, and tourist visits rose by 38% within the first two months after implementation. The Sport Tourism App 5.0 effectively enhanced digital capacity, strengthened social collaboration, and expanded the community’s economic impact. This initiative serves as a replicable model of technology-based community empowerment for other tourism villages in Indonesia.